The quality of BlaBlaCar’s services as perceived by its users - Ghirotti, Gabryela Martins; Oliveira, Rodrigo Ribeiro de (Brazilian Journal of Production Engineering, 2022)
This case study aims to identify the quality of the services offered by the ride sharing company/application, BlaBlaCar, from the perspective of Brazilian women. The research also addresses the woman who travels alone, the sharing economy and seeks to identify the perception of reliability of rides. To analyze the perception of Brazilian female users of BlaBlaCar on the quality of services, a documentary research was adopted, with the User Generated Content as the primary data source. A total of 300 comments posted during the months of January to March 2020, on the company’s app on the digital platform Google Play were analyzed and data collection was carried out in July 2021. The results showed that, despite problems with the functioning of the app itself, users approve of the quality of the company’s ride services, this being another possibility of displacement and use of the sharing economy for women traveling alone.